2011
DOI: 10.1038/jhg.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative association of eight susceptibility genes with systemic lupus erythematosus in a Japanese female population

Abstract: Although large-scale studies established many susceptibility genes to systemic lupus erythematosus (SLE), effect of each gene is not sufficiently large to be used alone to identify individuals with strong genetic predisposition. In this study, we analyzed the cumulative number of risk alleles at eight established susceptibility loci, HLA-DRB1, IRF5, STAT4, BLK, TNFAIP3, TNIP1, FCGR2B and TNFSF13, in 282 Japanese female SLE and 222 healthy female controls. The average number of risk alleles was significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Although each risk gene has a relatively low OR for disease susceptibility, the carriage of more risk alleles, in several risk genes, appears to increase the risk for disease susceptibility. Such cumulative associations have been shown in other autoimmune diseases [28], and now also here, by the discovery of the additive effect of alleles in C8orf13–BLK and STAT4 in increasing the risk for polymyositis/dermatomyositis.…”
Section: Discussionsupporting
confidence: 66%
“…Although each risk gene has a relatively low OR for disease susceptibility, the carriage of more risk alleles, in several risk genes, appears to increase the risk for disease susceptibility. Such cumulative associations have been shown in other autoimmune diseases [28], and now also here, by the discovery of the additive effect of alleles in C8orf13–BLK and STAT4 in increasing the risk for polymyositis/dermatomyositis.…”
Section: Discussionsupporting
confidence: 66%
“…The cumulative number of risk alleles is reported to be significantly increased in SLE relative to healthy controls in the Japanese population [23]. We did replicate this association in Japanese childhood-onset SLE.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, an association of the cumulative number of risk alleles and SLE has been reported in the United States and Japan [4], [23]. Koga et al analyzed the cumulative number of risk alleles at eight established susceptibility loci, namely HLA-DRB1 , IRF5 , STAT4 , BLK , TNFAIP3 , TNIP1 , FCGR2B and TNFSF13 , in a Japanese population.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic multisystem relapsing-remitting autoimmune disease, primarily affecting females [1], which can be influenced by hormonal, genetic and environmental factors [2][3][4][5][6][7]. Clinical studies have shown that neurologic and neuropsychiatric (NP) symptoms occur in up to 75% of patients, a condition representing a particularly severe form of the disease known as NPSLE [8].…”
Section: Introductionmentioning
confidence: 98%